HUMAN PSYCHE AND HEALTH ISSUES IN THE WORKS OF EASTERN THINKERS (International conference on multidisciplinary science, 2023)
Medical psychology, literally, is a science that studies patient psychology. Looking at the literature of the ancient period, we witness that the sciences of medicine, philosophy and psychology are closely intertwined. Almost all philosophers who lived before BC wrote down their opinions on medicine and psychology, since they associated the source of spiritual forces with the human brain. Abu Bakr ar-Rozi (R.865-925), a prominent thinker born in Iran.) left an indelible mark on the medical world. He was a great healer of his time, and historians write that he did not make mistakes in treating patients. He tested some new drug on animals before giving it to a patient. Rosey focused heavily on diet as well as mental effects in treating patients. He has completed many treatises on mizoj, paralysis, sex, hygienic activities and dorishunos [1].